Labour-Intensive Program: A Transformation of Public Welfare Policy in Supporting Sustainable Development - Chabibi, Muhammad (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2025)
The Labour-Intensive Program is a policy of the Surabaya City Government that is oriented towards empowering human resources and developing public welfare for low-income communities in the City of Surabaya after the COVID-19 pandemic. This research aims to describe; 1) the transformation of the Surabaya City Government’s public policy from a social welfare orientation to a labor-intensive policy after changes in the implementation of PERWALI No. 35 of 2022 concerning Amendments to the Surabaya Mayor’s Regulation Number 9 of 2022 concerning Social Rehabilitation of Uninhabitable Houses in the City of Surabaya; and 2) the implementation of the labor-intensive program policy. This research method is a qualitative-descriptive research with data collection techniques through literature studies, observations and in-depth interviews with policy implementers (Public Housing & Human Settlements Office) in the Dupak Village area, Krembangan District. This study produces several conclusions: 1) changes in the implementation of PERWALI NO. 35 of 2022 concerning Amendments to the Regulation of the Mayor of Surabaya Number 9 of 2022 concerning Social Rehabilitation of Uninhabitable Houses in the City of Surabaya, is the interest of the policy actor (Mayor of Surabaya) as a consequence of the shift in the policy paradigm from a social welfare-based program to a labor-intensive program. 2) The implementation of labour-intensive policies aims for public welfare in reducing poverty and unemployment, and national economic recovery in order to support sustainable development goals.